“Make the Separation Physical”: (De)legitimizing Black Separatism in Sutton E. Griggs’s Imperium in Imperio - Naughton Gerald David (American, British and Canadian Studies Journal)
The 1890s have often been described as perhaps the low point of the United States’ race relations. Sutton E. Griggs’s Imperium in Imperio (1899) imagines a complex solution to this racial nadir, a proto-Black Nationalist plot that would create an “empire within an empire.” The title of Griggs’s text acknowledges America’s imperial power, while also imagining an alternative narrative of utopianism. Furthermore, the novel anatomises the systematic removal of African Americans from the nation’s dream of a white future, offering a threatening antithesis to the ideals that sustain that future. However, the novel clearly does not present a model of doctrinaire nationalism, but rather a divided and unresolved striving for a new way out of America’s racial nightmare. Rather than producing a coherent solution, Griggs’s novel outlines various solutions to the problems of his age. Two approaches to black leadership, militancy and cooperation, are embodied by the novel’s two protagonists, Bernard Belgrave and Belton Piedmont, respectively. The novel ends oscillating irresolutely between ambiguous conciliation and fantasised insurrectionary threat: two resolutions that are crucially engendered by each character’s familial situation, and by each character’s relationship with the broader conceptual ‘family America.’ The novel finds only temporary resolution, or “philosophical pragmatism,” a provisional solution to a racial nightmare that centres on the persistently resonant dream of the American family.